Analysis of Physical and Chemical Quality of PDAM Water in Teluk Ambon Baguala Sub-District - Asry Nelannya Latupeirissa; Jolantje Latupeirissa (Jurnal Penelitian Pendidikan IPA, 2022)
A study has been carried out on the analysis of the physical and chemical quality of PDAM water in the Teluk Ambon Baguala sub-district. The purpose of this study was to analyze the physical and chemical quality of water from the Regional Drinking Water Company (PDAM) in Halong, Lateri, and Passo villages, including smell, taste, color, temperature, a total of dissolved solids (TDS), pH and hardness. The method used is the observation in the field at the time of sampling, then measurement and analysis in the laboratory. The results of the study indicate that the physical and chemical quality of PDAM water in the Teluk Ambon Baguala sub-district, which are smell, taste, color, total of dissolved solids (TDS), pH and hardness have met the drinking water quality standards according to the Regulation of the Minister of Health No. 492/Menkes/per/IV/2010.